Evaluación del comportamiento agronómico en brotes de nueve variedades de café arábiga (Coffea arabiga L) a partir de la primera recepa, en la granja experimental El Triunfo, cantón Caluma, provincia Bolívar - Angulo Angulo, Ariel Alejandro (2023)
The Bolívar province has a high potential for coffee production in the foothills and lower part towards the coast. The evaluation of the agronomic behavior in sprouts of nine coffee varieties from the first recipe was carried out at the Triunfo farm in the Caluma Canton, where the behavior of the nine varieties after the pruning of the recipe was evaluated, as well as the existence of pests and diseases in this crop was qualitatively characterized, finally the varieties that presented better development and vigor were identified. The problem in coffee cultivation focuses on low profitability, since in old coffee plantations, after several years, their production decreases. The reason why this research project was carried out was with the purpose of applying the rehabilitation technique in the cultivation of old coffee through recepting pruning. The following variables were evaluated: Days to sprouting after the first recepa, sprouting percentage, number of sprouts per plant, height of sprouts, diameter of the pots, number of branches, length of the branch, diameter of the branch, number of leaves, leaf length, petiole length, petiole diameter, plant vigor and incidence of anthracnose. The treatments under study were nine varieties of Arabica coffee with an agromorphological evaluation. The results obtained in each of the treatments under study presented mathematical and statistical differences, being T1 with 41 shoots per plant the one that stood out in the variable number of shoots per plant, followed by the variable height of the shoots being the T3 with 10,52 cm at 60 days and T9 with 40,42 cm at 120 days, in the variable diameter of the shoots was T3 with 0,47 cm at 60 days, which did not show statistical differences and T9 standing out with 1.14 cm at at 120 days, in the variable number of branches being T3 with 9 branches the one that showed a difference in relation to the other treatments at 120 days, in the variable branch diameter T4 with 0,69 cm at 120 days, in the variable number of leaves being the T1 with 7 leaves the same that did not show statistical differences at 60 days and being the T8 with 50 leaves the one that showed statistical differences at 120 days, in the variable length of the leaf being the T1 with 9,01 cm the one that did not show statistical differences at 60 days and T7 with 17.17 cm, which stood out the most in relation to the other treatments at 120 days, in the petiole length variable, being T1 with 0,41 cm the one that stood out in data collection at at 60 days and T5 with 1,59 cm at 120 days which did not present significant differences, in the petiole diameter variable T3 with 0,24 cm in the data collection at 60 days and T3 with 0,43 cm at 120 days , in the variable corresponding to plant vigor, T9 with a value on the scale of 4 at 60 days and T8 with a value on the scale of 4, the same that did not present significance at 120 days, finally in the variable incidence of anthracnose T6 with 100 % was the one that presented the greatest affectation in relation to the other treatments.